Model Latihan Untuk Mengurangi Keluhan Nyeri Punggung Bawah Akibat Kerja Pada Pengrajin Rotan (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2008)
Practice utilization to decrease waist pain complaint under in worker not yet common used among entrepreneur and worker in indonesia. while with do practice that accus-tommed with work attitude can be produced physical condition optimal to support good work productivity (Erchard, 1994). Based on researcher observation in place rattan Industrial, majority worker more like to take medicine and submit permission not enter work than do practice. This matter is among others caused by stills at least information and datas hit appropriate practice model with job type. One of the manner produces data and information with do watchfulness and then publicize watchfulness result. This watchfulness aims to detect appropriate practice model to decreases waist pain com-plaint under rattan worker. This watchfulness is experiment watchfulness at field, with watchfulness method as follows: first will determine rattan worker sample as much as 40 that be given two treatment kinds. Rattan worker a while ago then divided to be two treatment groups each consist of 20 person; that is treatment group a given practice program fleksi and waist extension follows william, while group b given practice eks-tention and fleksi waist follows mc kenzie. Treatment gift is carried out during 2 months. After researcher treatment gift compares waist pain complaint difference under deliver group at the (time) of before treatment and after treatment, then the result is compared with pain measurement that done before treatment gift. Waist pain measurement under use visual analogoe scale (vase). Sample taking by using technique purposive sampling, watchfulness design with pretest-postest design,Â  and data analysis uses test t and corre-lation. By the end of watchfulness shows that found difference very have a meaning towards pain quality before practice gift with pain quality after practice gift with standard signifikansi 0,0001 (p<0.05). Good practice model fleksi-ekstensi also ekstensi-fleksi waist can be used to decrease back pain under rattan worker with good result. Not found difference that have a meaning between practice model fleksi-ekstention with ekstensi-fleksi waist towards back pain complaint depreciation under.keywords: Practice Model, Back Pain Under, Rattan Worker